2018
DOI: 10.1007/s00402-018-2875-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterolateral tibial plateau fractures, how to buttress? Reversed L posteromedial or the posterolateral approach: a comparative cadaveric study

Abstract: The PL approach provides better access for buttressing the posterolateral tibial plateau fracture than the R-PM approach. With the R-PM approach, the blind area on the lateral plateau which can be accessed only by the PL approach starts approximately at 43.72% and ends at 81.41% of the lateral tibial plateau width. When a fracture is located in this zone, the posterolateral approach is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…Orapiriyakul et al compared the surgical exposure area between the Luo and the Yu (similar to the Carlson approach) approaches, and found the second to provide better exposure for buttressing the PL tibial plateau fracture. 28 For the reversed posteromedial approach, an approximately 10 cm L-shaped skin incision is made beginning at the center of the popliteal crease, curving distally at the medial corner of the popliteal fossa, and running along the posteromedial ridge of the tibial. 26 The medial head of the gastrocnemius muscle is retracted laterally protecting the popliteal neurovascular bundle.…”
Section: Surgical Techniques For Reconstruction Based On the Type Of mentioning
confidence: 99%
“…Orapiriyakul et al compared the surgical exposure area between the Luo and the Yu (similar to the Carlson approach) approaches, and found the second to provide better exposure for buttressing the PL tibial plateau fracture. 28 For the reversed posteromedial approach, an approximately 10 cm L-shaped skin incision is made beginning at the center of the popliteal crease, curving distally at the medial corner of the popliteal fossa, and running along the posteromedial ridge of the tibial. 26 The medial head of the gastrocnemius muscle is retracted laterally protecting the popliteal neurovascular bundle.…”
Section: Surgical Techniques For Reconstruction Based On the Type Of mentioning
confidence: 99%
“…Using variable angle -locking compression plates (VA-LCP) with a 30 degrees' cone allows us to diverge the VA-LCP locking (rafting) screws posteriorly through the fracture and ensure adequate fixation and articular support of extended lateral column fractures (Figure 1). Nevertheless, lateral ORIF does not always provide sufficient support of posterolateral (and posteromedial) column fractures (Figure 1) [11][12][13]. Surely enough, only 3/42 patients (7.1%) with a combined lateral and posterior column fracture were treated according to the TCC (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The common peroneal nerve was retracted gently to the lateral side and the lateral gastrocnemius was retracted to the medial side, so that the tension of retraction was mainly on the lateral gastrocnemius muscle and not the common peroneal nerve. This provides an adequate area for the fragments’ reduction and internal fixation by the buttress plate 13. Previous work in cadavers has demonstrated that, in isolated posterolateral tibial plateau fractures, it is possible to apply anatomical reduction and buttress plating on the posterior surface with a direct posterior split-gastrocnemius approach.…”
Section: Discussionmentioning
confidence: 99%